2011
DOI: 10.1007/s12031-011-9631-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Extracellular Proteasome in the Cerebrospinal Fluid: A Study on Concentration and Proteolytic Activity

Abstract: Alterations of the intracellular ubiquitin-proteasome pathway are found in neurodegenerative and inflammatory disorders of the central nervous system, as well as in its malignancies. Inhibitory substrates of the proteasomes represent promising approaches to control autoimmune inflammations and induction of apoptosis in cancer cells. Extracellular circulating proteasomes are positively correlated to outcome prognosis in hematogenic neoplasias and the outcome in critically ill patients. Previously, we reported r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 57 publications
(66 reference statements)
1
22
0
5
Order By: Relevance
“…EVs have been also suggested as the active delivery mechanism of biological mediators in peripheral blood and other bodily fluids of several diseases including MS162324. Hence, we investigate whether serum EVs might be responsible for the differences in extracellular proteasome concentration we observed in RRMS and CIS cohorts compared to healthy donor cohort.…”
Section: Resultsmentioning
confidence: 89%
“…EVs have been also suggested as the active delivery mechanism of biological mediators in peripheral blood and other bodily fluids of several diseases including MS162324. Hence, we investigate whether serum EVs might be responsible for the differences in extracellular proteasome concentration we observed in RRMS and CIS cohorts compared to healthy donor cohort.…”
Section: Resultsmentioning
confidence: 89%
“…The proteasome is widely acknowledged to localize in the nucleus and cytoplasm in eukaryotes (68). However, several recent investigations reported that a biologically active proteasome core is present in extracellular space, including the alveolar space (69,70), blood plasma (71), and cerebrospinal fluid (72). These data suggest that cells secrete/shed proteasome and/or proteasome subunits into the extracellular space, wherein the proteasome components may retain function.…”
Section: Discussionmentioning
confidence: 97%
“…Показано, что в ответ на различные воздействия происходит перераспределение протеасом в клетке [159][160][161]. Более того, при различных стрессовых воздействиях, например, при разного рода повреждениях или заболеваниях, включая различные формы рака, существенно увеличивается число внеклеточных 20S протеасом (в сыворотке крови, спинномозговой жидкости, жидкости бронхоальвеолярного лаважа) [162][163][164][165][166][167][168].…”
Section: способы регуляции убиквитин-независимой протеасомной деградацииunclassified